EFFECTIVENESS OF BUSINESS PROGRAM FOR INCREASING ACCEPTOR FAMILY INCOME (UPPKA) IN KEBUMEN DISTRICT - Defi Anggun Setyaningsih; Ramli Ramli; Diana Diana (Indonesian Journal of Social Work, 2022)
The study was used to measure the effectiveness of the UPPKA program in Kebumen Regency. Effectiveness refers to the assessment of a program by comparing the results of the program realization and the planned results previously determined. Research on the effectiveness of the UPPKA program in Kebumen Regency aims to obtain an overview of: 1) respondent characteristics, 2) program targeting accuracy, 3) program socialization, 4) program objectives, and 5) program monitoring. The study used descriptive quantitative methods. The study population was 246 people including all active UPPKA group leaders in Kebumen Regency. The sample is determined by random sampling technique. The number of samples obtained is 71 respondents, which is measured using the Slovin formula. Data collection techniques used are questionnaires and documentation studies. The measurement technique used is the Guttman scale. The validity test of the measuring instrument was tested with visible validity (face validity), reliability test using the Cronbach Alpha method. Furthermore, the results of the study were analyzed using descriptive statistical techniques. The results showed that the implementation of the UPPKA program in Kebumen Regency was very effective with a program effectiveness ratio of 85.7%. The accuracy of program targets is 86.4%, program socialization is 87%, program objectives are 89.9%, and program monitoring is 78.7%. The causes for the less than optimal effectiveness were the inaccuracy of the implementation of program socialization, program monitoring, and program evaluation, the development of the UPPKA group was not optimal, and the respondents' low awareness and understanding of the business bookkeeping of the UPPKA group. In connection with these problems, the authors propose the program "Optimization of the UPPKA Group through "UPPKA Bangkit" in Kebumen Regency". The existence of this program is expected to improve all aspects of the effectiveness of the UPPKA program.